2003
DOI: 10.1103/physrevb.68.214404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic transitions in disorderedGdAl2

Abstract: The role of disorder in magnetic ordering transitions is investigated using mechanically milled GdAl 2 . Crystalline GdAl 2 is a ferromagnet while amorphous GdAl 2 is a spin glass. Nanostructured GdAl 2 shows a paramagnetic-to-ferromagnetic transition and glassy behavior, with the temperature and magnitude of each transition dependent on the degree and type of disorder. Disorder is parametrized by a Gaussian distribution of Curie temperatures T C with mean T C and breadth ⌬T C . A nonzero coercivity is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
2
26
1
Order By: Relevance
“…20 T C is essentially independent of the measuring field; however, ⌬T C depends on measuring field as H 1/ where ϳ 1 -1.5 for GdAl 2 . 20 Two effects shown in Fig. 5 must be explained: the shift in T C and the broadening of the transition with milling time.…”
Section: B the Pm-fm Transitionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 T C is essentially independent of the measuring field; however, ⌬T C depends on measuring field as H 1/ where ϳ 1 -1.5 for GdAl 2 . 20 Two effects shown in Fig. 5 must be explained: the shift in T C and the broadening of the transition with milling time.…”
Section: B the Pm-fm Transitionmentioning
confidence: 99%
“…The broadening is attributed to the distribution of local environments created by disorder. T C cannot be determined accurately from the minimum of dM͑T͒ / dT, and instead is found by fitting M͑T͒ to a distribution of Curie temperatures: [20][21][22] …”
Section: A the Paramagnetic Regimementioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the relationship between the structural and magnetic changes induced by the milling process results in the evolution from a ferromagnetic behavior to a spin-glass phase, which emerges at lower temperatures. [4][5][6][7][8] More recently, a study of the magnetic properties of TbAl 2 milled alloys has revealed that not only disorder but also size effects are important in crucial understanding of the magnetic behavior, with a pronounced variation of coercivity with the grain size. 9 The relevance of the extension of these studies of nanocrystalline particle systems to Ce and Yb intermetallics, the latter being known as strongly correlated electron materials, requires some understanding of how macroscopic properties in these systems become modified at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%